2017
DOI: 10.1016/j.ajpath.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Early Growth Response 1 in the Hippocampus Alleviates Neuropathology and Improves Cognition in an Alzheimer Model with Plaques and Tangles

Abstract: A sporadic form of Alzheimer disease (AD) and vascular dementia share many risk factors, and their pathogenic mechanisms are suggested to be related. Transcription factor early growth response 1 (Egr-1) regulates various vascular pathologies and is up-regulated in both AD brains and AD mouse models; however, its role in AD pathogenesis is unclear. Herein, we report that silencing of Egr-1 in the hippocampus by shRNA reduces tau phosphorylation, lowers amyloid-β (Aβ) pathology, and improves cognition in the 3xT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…More recently, EGR1 has also been implicated as a driving factor of AD neuropathology and cognitive decline, since hippocampal EGR1 inhibition was shown to reduce tau phosphorylation, lower Aβ pathology, and improve cognition in 3xTG-AD mice [ 183 ]. Since EGR1 inhibition was also shown to activate BACE1 activity [ 184 ], this calls for further studies into the role of (early life) modulation of EGR1 and its implication in cognitive impairment and AD neuropathology.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, EGR1 has also been implicated as a driving factor of AD neuropathology and cognitive decline, since hippocampal EGR1 inhibition was shown to reduce tau phosphorylation, lower Aβ pathology, and improve cognition in 3xTG-AD mice [ 183 ]. Since EGR1 inhibition was also shown to activate BACE1 activity [ 184 ], this calls for further studies into the role of (early life) modulation of EGR1 and its implication in cognitive impairment and AD neuropathology.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent studies reported Egr1 protein elevations in cognitively-impaired Tg2576, APP/PS1 and 3xTg-AD mouse models of AD [ 4 , 19 , 26 ]. Conversely, knockdown of EGR1 improved cognitive deficits in 3xTgAD mice [ 46 ]. Overall, these studies suggest that sustained elevated expression of EGR1 is detrimental for long-term memory.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these proteins are Low Density Lipoprotein Receptor-Related Protein 1 (LRP1), a cholesterol receptor that mediates endocytosis and binds to over 40 ligands [86], Epidermal Growth Factor Receptor (EGFR), a receptor tyrosine kinase in the neuregulin/ERBB family[87], 14-3-3beta (YWHAB), a phosphoserine/phosphotyrosine binding protein of the 14-3-3 family that interacts with a wide-range of other proteins to facilitate protein interactions [88], Small Ubiquitin Related Modifier 1 (SUMO1), a ubiquitin-like post-translational modification that affects a broad range of protein functions [89], and Early Growth Receptor 1 (EGR1), a transcription factor that represents an intermediate-early gene marking neuronal activation and synaptic plasticity [90]. All five of these proteins have been implicated in AD pathogenesis: LRP1 is a receptor that interacts with Abeta and APOE, which may influence LRP1's ability to aid in Abeta clearance [86]; EGFR polymorphisms were found to be inversely proportional to AD risk in a Han Chinese cohort [91]; 14-3-3 can be found around Abeta plaques and facilitates GSKbeta-mediated phosphorylation of tau [92]; SUMO1 expression is altered in cortices of AD patients [93]; and EGR1 inhibition leads to decreased Abeta and p-tau while reversing cognitive deficits in 3xTg AD mice [94]. However, the links between these proteins and HIDA Domain symptoms are sparse.…”
Section: Hida Domainmentioning
confidence: 99%